ANALISIS TATA LETAK FASILITAS PRODUKSI PADA PABRIK TAHU ANUGERAH CIPTA NUSANTARA DI KECAMATAN MEDAN SELAYANG MEDAN - Purba, Saut; Sihombing, Sarimonang; Parhusip, Poltak T. (UNIKA Santo Thomas, 2023)
The purpose of this study was to find out the layout of production facilities that can guarantee the smooth running of the production process at the Anugerah Cipta Nusantara tofu factory in Medan Selayang District, Medan. The total sample is all employees of the Tofu Factory Anugerah Cipta Nusantara. Analysis technique with qualitative descriptive analysis.The results showed that the layout used by Anugerah Cipta Nusantara tofu factory was a line layout (line layout) because it was considered easier to transfer raw materials and more focused in supporting the smooth production process. Laying out production facilities used can streamline time in the production process so that there is no wastage of time in preparing tofu production materials which can increase production results. The advantage of the line layout is that it is easy to set up production facilities located in the tofu factory and the materials produced are quickly processed and the supervision aspect is relatively easy so that the line layout is the layout of choice to apply. It is best if the Anugerah Cipta Nusantara tofu factory produces quality tofu at competitive prices and increases production volume, number of employees and provides modern machines considering that tofu consumers are increasingly in demand.